The Effects of Lucilia sericata Larvae and Eisenia fetida Earthworm Extracts Either Alone or in Combination on Healing Third-Degree Burns in Male Mice - Radin Reisi; Masih Sharifzadeh Esfarjani; Alireza Gandomkar; Amirmohammad Mahsa; Hossein Salehi; Parham Reisi; Zahra Jokar (Advanced Biomedical Research)
Background: Burn as the most common injury disrupts the protective function of the skin and induces complications in patients. Therefore, the treatment of these patients presents a significant clinical challenge. This study evaluated the effects of Lucilia sericata (L. sericata) larvae and Eisenia fetida (E. fetida) earthworm extracts, alone or in combination, on the healing of third-degree burns in male mice. Materials and Methods: A third-degree burn model was induced on the skin of the interscapular region. Then, the extracts of larvae and earthworms were topically applied separately or simultaneously every other day for a 21-day period. To evaluate the process of wound healing, macroscopic parameters were monitored and examined during the study period. Finally, the animals were sacrificed, and skin sampling was performed for histological investigations. Results: The results of the study showed that both extracts of larvae and earthworm accelerated the wound-healing process (P < 0.01). The group receiving extract of earthworm had better wound healing than the groups receiving Vaseline and silver sulfadiazine, and histological evidences confirmed these observations. However, the use of two extracts simultaneously did not affect the wound-healing process. Conclusion: The results of this study demonstrated that the extracts of L. sericata larvae and E. fetida earthworm, especially E. fetida, include effective compounds that can significantly enhance the rate of burn wound healing. However, more studies are needed to identify and purify the effective compounds of these extracts involved in the process of wound healing.